2014
DOI: 10.1093/bioinformatics/btu166
|View full text |Cite|
|
Sign up to set email alerts
|

relax: the analysis of biomolecular kinetics and thermodynamics using NMR relaxation dispersion data

Abstract: Nuclear magnetic resonance (NMR) is a powerful tool for observing the motion of biomolecules at the atomic level. One technique, the analysis of relaxation dispersion phenomenon, is highly suited for studying the kinetics and thermodynamics of biological processes. Built on top of the relax computational environment for NMR dynamics is a new dispersion analysis designed to be comprehensive, accurate and easy-to-use. The software supports more models, both numeric and analytic, than current solutions. An automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Relaxation dispersion curves obtained at two static magnetic fields were generated by plotting R 2 vs. 1/τ cp using GraphPad Prism 7.0 (GraphPad Software) and fit simultaneously using the fast-limit CPMG equation, where uncertainty values were obtained from replicate spectra. Dual field relaxation dispersion data were also processed with RELAX (41-43) using the R2eff, NoRex, and MMQCR72 (two-site Carver-Richards) models (44). Relax was used to globally fit residues undergoing dispersion in V12A, K19A, V48A, and D98A IGPS, and statistical analyses of independent and global models indicated that only V12A IGPS was well-described by a global dynamic process based on the Akaike information criterion (28,45,46).…”
Section: Methodsmentioning
confidence: 99%
“…Relaxation dispersion curves obtained at two static magnetic fields were generated by plotting R 2 vs. 1/τ cp using GraphPad Prism 7.0 (GraphPad Software) and fit simultaneously using the fast-limit CPMG equation, where uncertainty values were obtained from replicate spectra. Dual field relaxation dispersion data were also processed with RELAX (41-43) using the R2eff, NoRex, and MMQCR72 (two-site Carver-Richards) models (44). Relax was used to globally fit residues undergoing dispersion in V12A, K19A, V48A, and D98A IGPS, and statistical analyses of independent and global models indicated that only V12A IGPS was well-described by a global dynamic process based on the Akaike information criterion (28,45,46).…”
Section: Methodsmentioning
confidence: 99%
“…Relaxation dispersion curves were generated by plotting R 2 vs. 1/ τ cp using RELAX(Bieri et al, 2011; d’Auvergne et al, 2008a, b) with the R2eff, NoR ex , and MMQCR72 (full two-site Carver-Richards) models. (Morin et al, 2014) Relaxation dispersion data obtained at two static magnetic fields were fit simultaneously using the fast CPMG Equation and uncertainty values were obtained within RELAX from replicate spectra.…”
Section: Experimental Nmr Proceduresmentioning
confidence: 99%
“…However, the REC residues, such as Ile 3 , Gly 24 , Val 26 , Cys 27 , Asp 28 , Ser 46 , Ile 127 and Val 136 , which are located in the REC-DBD interface, exhibit only one set of NMR resonances in the DNA-bound state (Fig. 4a-c).…”
Section: Resultsmentioning
confidence: 99%
“…11). Measurements at both 600 and 850 MHz were fitted individually by use of the software relax 28 to a two-site exchange process (A2B), yielding populations (p A and p B ), exchange rate constants (k ex ¼ k AB þ k BA ) and the 1 H and 13 C chemical shift differences between the two states 27 (Supplementary Table 4). In total, 12 PmrA methyl groups exhibit slow dynamics on binding to DNA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation